Extremely Preterm Infants Have a Higher Fat Mass Percentage in Comparison to Very Preterm Infants at Term-Equivalent Age - Bruckner, Marlies; Khan, Zahra; Binder, Christoph; Morris, Nicholas; Windisch, Bernadette; Holasek, Sandra; Urlesberger, Berndt (Frontiers in Pediatrics, 2020)
Background: Early nutritional support of preterm infants is important because it influences long-term health and development. Body composition seems to have an influence on cardiovascular disease, metabolic syndrome and neurocognitive outcome in the long term. Objective: To assess body composition in preterm infants <32 weeks of gestation at term- equivalent age and to analyze the influence of an optimized nutritional approach. Methods: This is a prespecified secondary outcome analysis of a prospective observational study comparing the body composition in regard to gestational age. The preterm infants were classified according to gestational age as extremely preterm infants (<28 weeks gestation at birth) and very preterm infants (≥28 weeks gestation at birth) and according to weight percentile as appropriate for gestational age and small for gestational age. Body composition was determined by air displacement plethysmography using the PEA POD. The preterm infants obtained nutrition according to the ESPGHAN 2010 Guidelines. Results: 74 preterm infants were analyzed. The mean (SD) gestational age was 28.7 (2.4) weeks and birth weight was 1162 (372) grams. Fat mass percentage was significantly higher in extremely preterm infants in comparison to very preterm infants (17.0, 95%CI 15.9 to 18.1 vs. 15.5, 95%CI 14.7 to 16.2). There was no significant difference of fat mass percentage according to weight percentiles. Postnatal age correlated positively with the fat mass percentage of preterm infants (p≤0.001; r2=0.71). Conclusions: Extremely preterm infants had a significantly higher FM% compared to very preterm infants at term- equivalent age. The nutritional regimen in our cohort seems to be adequate in order to optimize neurocognitive development.